The command to Marry is Formulated in a Hadith: O young men, whoever among you is able to marry, let him Marry A Comparative Jurisprudential Study (Islamic Sciences Journal, 2023)
ABSTRACT             This research entitled “The Order to Marry in Sahih Muslim - A Comparative Fiqh Study” indicates a jurisprudential ruling that the jurists dealt with in clarification and detail, which is the ruling on marriage, and this topic deserves study and research; Because it is closely related to the life of humanity  So the researcher began to embark on this subject with the hadiths in which the command to marry was mentioned, so does the ordering formula make it obligatory? Or on the scar? Or on permissibility?, Then the researcher touched on highlighting the position of the jurists and their opinions on this subject, presenting and discussing their evidence to come up with a sound opinion and a middle one among those opinions  Therefore, the research was divided into an introduction, two chapters, and a conclusion, where the researcher mentioned in the introduction the importance of the research. In the first topic, the researcher dealt with the definition of the terms of the title, where the researcher touched on the definition of the matter, marriage, language and terminology, the definition of Imam Muslim, and his book (Sahih Muslim). Then, in the second topic, the researcher dealt with: the matter of marriage and its ruling, by mentioning the sayings of the jurists and their evidence, and among the conclusion of the research was a set of results reached by the researcher.
Keywords: The Order, Imam Muslim, Marriage, Differences of Jurists, Sahih Muslim Book..